Extracellular vesicles in renal cell carcinoma: challenges and opportunities coexist - Lu, Yukang; Zhang, Mengting; Zhou, Jiajun; Liu, Xiulan; Wang, Lanfeng; Hu, Xinyi; Mao, Yiping; Gan, Rongfa; Chen, Zhiping (Frontiers in Immunology, 2023)
Renal cell carcinoma (RCC) represents an extremely challenging disease in terms of both diagnosis and treatment. It poses a significant threat to human health, with incidence rates increasing at a yearly rate of roughly 2%. Extracellular vesicles (EVs) are lipid-based bilayer structures of membranes that are essential for intercellular interaction and have been linked to the advancement of RCC. This review provides an overview of recent studies on the role of EVs in RCC progression, including involvement in the interaction of tumor cells with M2 macrophages, mediating the generation of immune tolerance, and assuming the role of communication messengers in the tumor microenvironment leading to disease progression. Finally, the " troika " of EVs in RCC therapy is presented, including engineered exosomal or EVs tumor vaccines, mesenchymal stem cell EVs therapy, and reduction of tumor-derived EVs secretion. In this context, we highlight the limitations and challenges of EV-based research and the prospects for future developments in this field. Overall, this review provides a comprehensive summary of the role of EVs in RCC and their potential as a viable pathway for the future treatment of this complex disease.